Female Narcissism: Assessment, Aetiology, and Behavioural Manifestations. Issue 6 (December 2022) - Green, Ava; MacLean, Rory; Charles, Kathy
Despite putative gender differences in the expression of narcissism, prominent theories have virtually dismissed the role of females in the development and manifestation of narcissism. The contention that narcissism is a pathology of the self that may partly differ in males and females is further evident in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). The DSM-5 reports that up to 75% of those diagnosed with Narcissistic Personality Disorder (NPD) are men. Such figures suggest that the representation of narcissism as codified in the DSM-5 may only be marginally applicable to females, given its prominent focus and nature on capturing grandiose themes which closely resemble commonly masculine norms. The overemphasis on grandiose features extends to the empirical literature which defines narcissism as a normative personality trait and is widely assessed using the Narcissistic Personality Inventory (NPI), on which males obtain significantly higher scores than females. As this review will demonstrate, one limitation frequently occurring in the literature is the attempt to comprehend narcissistic manifestations in females through the lens of what has commonly been defined as narcissism (DSM/NPI). In this review, the literature concerning the diagnostic assessment and conceptualisation of narcissistic personality disorder, aetiological factors, aggression, and partner violence perpetration will be discussed in relation to the importance of gender. This is followed by a review of existing gaps in theory and research, and suggestions for fruitful directions that can aid a richer and more meaningful literature on narcissism inclusive of gender issues.